Efficacy and safety of greater occipital nerve block for the treatment of cervicogenic headache: a systematic review. (4th May 2021) - Caponnetto, Valeria; Ornello, Raffaele; Frattale, Ilaria; Di Felice, Chiara; Pistoia, Francesca; Lancia, Loreto; Sacco, Simona
ABSTRACT: Introduction: Cervicogenic headache (CGH) is a secondary headache disorder caused by cervical spine or neck soft tissue lesions. Despite few available evidence-based pharmacological treatments are available, greater occipital nerve blocks (GONBs) are considered as therapeutic option. Area covered: In June 2020, we conducted a systematic review on Pubmed and Scopus, to summarize effectiveness and safety of GONBs in treating CGH. We included 5 observational studies and 3 nonrandomized trials reporting clinical outcomes of 140 CGH patients after GONBs. Authors performed unilateral GONBs during interictal phase (five studies) or during pain, injecting local anesthetic (four studies) or both local anesthetic and steroid (three studies) at variable timepoints. In 5 studies mean pain reduction ranged from −8.2 (at 2 weeks after the first block) to −0.1 (at 1 month after the third block); one study documented 66.6% reduction of pain intensity and another study documented a significant median reduction of pain intensity at 3 months (decreased from 5.5 to 2.3) and not at 9 months. Three studies reported minor adverse events. Expert opinion: Few available studies suggest that GONBs are effective and safe in treating CGH. GONB is a high tolerable, low cost and repeatable procedure. Larger and randomized studies are needed.